2015
DOI: 10.1155/2015/230808
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoreduction Activity of Carbon Dioxide over Co3O4/CeO2Catalysts under Visible Light Irradiation

Abstract: A series of new two semiconductor catalysts, Co3O4/CeO2, were prepared by glycine-nitrate combustion method for photocatalytic reduction of carbon dioxide to produce methanol and ethanol under visible light (λ>400 nm) irradiation. The catalysts were characterized by BET, UV-vis spectra, XRD, SEM, PL, and XPS and the results indicated that the catalyst with 5 wt.% of Co3O4has the highest yield among all kinds of tests with the methanol yield of 1.52 μmol·g−1·h−1and the ethanol yield of 4.75 μmol·g−1·h−1, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The similar absorption spectra were earlier reported for CeO 2 [28][29][68][69][70]. Strong ultraviolet absorption capability of cerium oxide is related to the charge transfer from O 2to Ce 4þ ions.…”
Section: Absorption and Emission Spectrasupporting
confidence: 87%
“…The similar absorption spectra were earlier reported for CeO 2 [28][29][68][69][70]. Strong ultraviolet absorption capability of cerium oxide is related to the charge transfer from O 2to Ce 4þ ions.…”
Section: Absorption and Emission Spectrasupporting
confidence: 87%
“…The band gaps of these three powders are shown in Figure B, and the value for c ‐CeO 2 is 3.2 eV, whereas it is 2.7 eV for m ‐CeO 2 and its aged powder. The band gap of ceria is different depending on the synthesis methods and the particle size, Huang et al reported that the band gap of ceria particle was 2.7‐3.4 eV, and in Verma's report bulk ceria's band gap was 3.2 eV. The method to lower the band gap is one or a combination of techniques such as (1) introduction of intrinsic defects into the system, (2) doping by complementary atoms, (3) deposition of plasmonic resonant materials over the system, and (4) developing intrinsic homocomposite of heterophasic, mixed phase/biphasic ceria system .…”
Section: Resultsmentioning
confidence: 99%
“…CeO 2 catalyst was prepared by glycine-nitrate combustion method as our preview work [22,23]. The powder was characterized after calcined at 300 °C, 400 °C, 500 °C, 600 °C, respectively.…”
Section: Methodsmentioning
confidence: 99%